Gospodarka i społeczeństwo carskiej Rosji wobec przyszłej wojny totalnej. Predykcje Jana Gottlieba Blocha - Pieczewski, Andrzej (Wydawnictwo Uniwersytetu Rzeszowskiego, 2015)
The aim of this article is to present John Bloch’s (1863–1902) analysis contained in the book Future War. This analyses concerns the behavior of Russian economy and society in the context of future total war (WWI). The author concludes that Tsarist Russia should better overcome war difficulties than other Western European countries. His claims were based on assumptions that societies of richer countries would hardly bear the inconvenience the war brings them. The poorer and less civilized Russian society and less developed Tsarist economy could bear more. Therefore Bloch claimed that the threat of socialist revolution refered more to Western Europe. His predictions turned out to be false. Financing and food supply for the large Russian army led to the impoverishment of society and hunger. As a result, the socialist revolution broke out in Tsarist Russia.
Economy and society of tsarist Russia towards the future total war. Predictions of John Bloch
Keywords: World War I; economy of Tsarist Russia; John Bloch